Penetration enhancer containing vesicles for dermal and transdermal drug delivery. A review - Fatma A. Sarhan; Riham I. El-Gogary; Manal Yassin Hamzaa; Mahmoud E. Soliman (Archives of Pharmaceutical Sciences Ain Shams University)
Dermal and transdermal drug delivery systems are attractive dermatological products of great importance in the pharmaceutical market from conventional to advanced formulations. The skin, the largest organ in our body, has a barrier function to protect our bodies against any harmful external factor. This function may interfere or totally inhibit the drug delivery through the skin. Therefore, for efficient drug penetration or permeation two approaches can be applied; adding external penetration enhancers to ease the drug penetration, or to encapsulate the drugs in carrier systems that facilitate drug penetration by squeezing through skin tight junctions hence allowing better penetration of drug. Hence, researchers have developed novel ultra-deformable nano-vesicles to overcome this barrier function of the skin and deliver the drug to the required action site. Among the most promising developed nano-vesicles are the lipid based nanocarriers. The penetration enhancer containing vesicles are lipid-based nano-vesicles containing penetration enhancers hence combining both aforementioned approaches for facilitating drug penetration through the skin. This review gives an overview on one of the novel ultra-deformable vesicles; the penetration enhancer containing vesicles (PEVs) which are used in dermal and transdermal drug delivery with special emphasis on their composition and method of preparation. A special focus was made on the therapeutic outcome of using penetration enhancers containing vesicles compared to the conventional dosage forms.